Toughness, elasticity and physical properties for the evaluation of foamed concrete reinforced with hybrid fibers - Dawood, Eethar Thanon; Yahya Ziad, Mohammad; Waleed, Abdulrazzak Abbas; Mohammad, Abdul Mannan (Elsevier Ltd, 2018)
This study has been undertaken to investigate the evaluation of Fiber-reinforced Foamed Concrete (FRFC) performance by the use of toughness and nondestructive tests. These tests cover the workability, density, static modulus of elasticity, toughness, ultrasonic pulse velocity and absorption tests. Different FRFC mixes using carbon fibers in the order of 0.5, 1 and 1.5% carbon fibers were used. Also, the combinations of carbon fibers (C) and polypropylene fibers (PP) as 1% Cþ 0.5% PP, and 0.5% Cþ1% PP were prepared. Lastly, the inclusion of polypropylene fibers with the order of 1.5% PP was used to strengthen the foamed concrete mix. The results showed that the use of 1.5% of C has affected the modulus of elasticity and flexural toughness of foamed concrete. On the other hand, a strong relationship is found between compressive strength and ultrasonic pulse velocity for FRFC.